Effect Of Red Onion (Allium Cepa) Peel Extracts And Fractions On Cell Proliferative And Metastatic Activities In Mda-Mb-231 - Siah, Poh Chiew (2017)
The present study was conducted with the objective to study the anti-cancer property of red onion (Allium cepa) peel extracts and its fractions by investigating the effects in MDA-MB-231, MCF-7 and Cal-27. The effects of red onion peel extracts and its fractions in the anti-proliferative activity, induction of apoptosis - programmed cell death and anti-metastasis were studied. In addition, the involvement of Wnt signalling pathway in the anti-cancer activity of red onion peel extracts and its fractions was also investigated. In the results, the extracts (E1 and E3) and fractions (F1, F2, F1W and F2W) showed promising inhibitory effect on cell viability of MDA-MB-231.